Comparison of Efficacy of Remdesivir with Supportive Care Alone in the Treatment of Critically Sick Adult and Child COVID-19 Patients: A Randomized Clinical Trial - Hormati, Ahmad; Ahmadpour, Sajjad; Ghadir, Mohammad R.; Ghomi, Seyed Yaser Foroghi; Tafaroji, Javad; Movahedi, Zahra; Hossaini, Seyed Kamal Eshagh; Khoshgoftar, Morteza; Gheitani, Mina (Anti-Infective Agents, 2023)
Background: Seeking new specific and effective drugs against Coronavirus Diseases-2019 (COVID-19) is of great importance. This study describes the efficacy of remdesivir with supportive care alone in the treatment of critically sick adult and child COVID-19 patients. Methods: This study was a one-blind placebo-controlled, randomized clinical trial in adults (aged≥18 years) and children (aged≤12 years) in Iran. Patients were included if they had positive PCR test for SARS-CoV-2 infection, O2 saturation ≤88%, and compatible symptoms. All participants received standard care following national treatment guidelines. The treatment group received remdesivir (200 mg IV on day 1 and followed by 100 mg in single daily infusions). The control group received standard care and an identical volume of placebo infusions (Water for injection) for 5 days. For pediatric patients, the intervention group received remdesivir (5mg/kg on the first day and then 5.2 mg/kg on days 2 to 5). Discharge from the hospital within 10 days of first treatment is considered as the primary endpoint of the study. Admission in the intensive care unit (ICU) is considered as original secondary endpoint of the study. Results: 141 patients were enrolled and randomly assigned to two group (adults; 54 patients in the intervention group vs. 52 patients in the control group, and children; 17 patients in the intervention group vs. 18 patients in the control group). The mean time from the first symptoms until the referral to the hospital in adult patients was 5.61 ± 2.67 day and 4.80±1.48 day for intervention and control groups, respectively. The mean time from the first symptoms until death was reported to be significant and was longer for intervention group than the control group (24.83 ± 11.25 vs. 10.50 ± 2.42 day; p value=0. 012). For children who received remdesivir, the mean time between admission until death was reported to be significant, as the finding highlighted a longer time duration for the intervention group (13.55 ± 0.72 vs. 10.66 ± 0.57 day; p value=0. Mechanicalanical ventilation was used in 17 patients (100%) and 18 patients (100%) in the intervention and control groups, respectively (p value=0.853). Conclusion: Among patients with critical COVID-19, those randomized to a 5-day treatment of remdesivir did have a statistically significant difference in clinical status compared with the control group of both adults and children.
Keywords: mechanical ventilation